2022
DOI: 10.1186/s13244-022-01199-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of fully-automated and semi-automated artificial intelligence methods for the detection of clinically significant prostate cancer on MRI: a systematic review

Abstract: Objectives We systematically reviewed the current literature evaluating the ability of fully-automated deep learning (DL) and semi-automated traditional machine learning (TML) MRI-based artificial intelligence (AI) methods to differentiate clinically significant prostate cancer (csPCa) from indolent PCa (iPCa) and benign conditions. Methods We performed a computerised bibliographic search of studies indexed in MEDLINE/PubMed, arXiv, medRxiv, and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…Moreover, PCa detected by established predictors of tumor progression such as PSA level elevation alone often results in higher false-positive rates, thus causing excess costs and potential risks related to unnecessary biopsies. 39 Recent studies do not only suggest that AI-based algorithms derived from mpMRI are able to differentiate between ncsPCa, csPCa, and benign prostatic alterations 40 and are capable of detecting tumors on histopathological level comparable to expert pathologists 41 but could already show advances in false positive reduction 25 which gains importance rapidly with 25% PCa per PSA elevation (>4 ng/mL 42 ) and a total of estimated 1.4 million diagnoses worldwide in 2020. 43 The use of AS has increased drastically over the last decades, for example, from 14.5% in 2010 to 42.1% in 2015 in the US population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PCa detected by established predictors of tumor progression such as PSA level elevation alone often results in higher false-positive rates, thus causing excess costs and potential risks related to unnecessary biopsies. 39 Recent studies do not only suggest that AI-based algorithms derived from mpMRI are able to differentiate between ncsPCa, csPCa, and benign prostatic alterations 40 and are capable of detecting tumors on histopathological level comparable to expert pathologists 41 but could already show advances in false positive reduction 25 which gains importance rapidly with 25% PCa per PSA elevation (>4 ng/mL 42 ) and a total of estimated 1.4 million diagnoses worldwide in 2020. 43 The use of AS has increased drastically over the last decades, for example, from 14.5% in 2010 to 42.1% in 2015 in the US population.…”
Section: Discussionmentioning
confidence: 99%
“…MRI quality and radiologist experience are variable and may have a direct impact on outcomes, in the future computer-aided diagnosis (CAD) systems may help reduce this variability, initial studies have shown promise in this area. However, these have demonstrated methodological limitations and biases which future studies will need to address to ensure generalisability [44]. Finally, all the risk models we tested were developed prior to the era of pre-biopsy MRI and we have assumed a similar proportion of deaths for the new simulated risk groups which may therefore be under or over estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing subtle changes in prostate, kidney, and bladder images can enhance early detection of urologic cancers, identification of the extent and stage of malignant tissues, and even predict tumor aggressiveness and responsiveness to treatment. The quantitative nature of radiomics allows for more consistency in radiographic assessment, minimizing inter-observer variability and enhancing diagnostic capabilities [3][4][5]. This review provides an overview of the most recent advancements in the domain of AI-powered radiomics applied to the field of urologic oncology, focusing on prostate, kidney, and bladder malignancies.…”
Section: Introductionmentioning
confidence: 99%